2015
DOI: 10.2147/ijn.s73780
|View full text |Cite
|
Sign up to set email alerts
|

Response of human mesenchymal stem cells to intrafibrillar nanohydroxyapatite content and extrafibrillar nanohydroxyapatite in biomimetic chitosan/silk fibroin/nanohydroxyapatite nanofibrous membrane scaffolds

Abstract: Incorporation of nanohydroxyapatite (nHAP) within a chitosan (CS)/silk fibroin (SF) nanofibrous membrane scaffold (NMS) may provide a favorable microenvironment that more closely mimics the natural bone tissue physiology and facilitates enhanced osteogensis of the implanted cell population. In this study, we prepared pristine CS/SF NMS, composite CS/SF/nHAP NMS containing intrafibrillar nHAP by in situ blending of 10% or 30% nHAP before the electrospinning step, and composite CS/SF/nHAP NMS containing extrafib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…The amplified PCR products were analyzed by ethidium bromide staining after 1.5% agarose gel electrophoresis. The PCR primers were designed with the Oligo 7 primer design software [ 32 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The amplified PCR products were analyzed by ethidium bromide staining after 1.5% agarose gel electrophoresis. The PCR primers were designed with the Oligo 7 primer design software [ 32 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both synthetic and natural materials have been electrospun for bone regeneration [ 16 - 18 ]. Polymers alone have been shown to be effective in the regeneration of bone.…”
Section: Nanofibresmentioning
confidence: 99%
“…The incorporation of nanohydroxyapatite (nHAP) with scaffolds has been shown to create a more favourable microenvironment that closely mimics the natural bone state has also been shown with other combinations of biomaterials [ 22 ]. Chitoson/silk fibroin scaffolds with nHAP nanofibrous membrane also promoted the osteogenic differentiation of hMSCS [ 16 ]. Collagen/nHA/PPLA scaffolds also demonstrated that the incorporation of nHA supported bone formation to a greater degree than poly-L-lactide (PLLA)/Col and PLLA/HA scaffolds [ 22 ].…”
Section: Nanofibresmentioning
confidence: 99%
“…These polymer scaffolds have been used for numerous applications, including regeneration of blood vessels (i.e. coronary arteries), bone, skin, cartilage, as well as to enhance cell proliferation and differentiation [3][4][5]. Another material that has shown rapid expansion among biocompatible scaffolds are electroactive materials.…”
Section: Introductionmentioning
confidence: 99%